An Analysis Of Illocutionary Acts Used In The Movie Entitled “A Tourist’s Guide To Love” - Ni Kadek Anggi Andriani; Komang Dian Puspita Candra (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This research aimed about the types of illocutionary acts found in A Tourist’s Guide To Love movie. The researcher used the theory from Searle (1976) in order to find out the types of illocutionary acts. Meanwhile, to analyze the meaning based on the context of situation, the researcher used the theory from Halliday and Hassan (1985). The main data source of this study is A Tourist’s Guide To Love movie. Observation method and note taking technique are used in this study to collect the data. This study used descriptive qualitative method in analyzing the types of illocutionary acts and the meaning based on the context of situation.In this research there were found in A Tourist’s Guide To Love movie. All the types of illocutionary acts werefound in this research which are Assertive, Directive, Commissive, Expressive and Declarative. Themeaning of illocutionary acts supported by the context of situation which are Field, Tenor and Mode.